Aerobic exercise, an effective prevention and treatment for mild cognitive impairment - Huang, Baiqing; Chen, Kang; Li, Ying (Frontiers in Aging Neuroscience, 2023)
Aerobic exercise has emerged as a promising intervention for mild cognitive impairment (MCI), a precursor to dementia. The therapeutic benefits of aerobic exercise are multifaceted, encompassing both clinical and molecular domains. Clinically, aerobic exercise has been shown to mitigate hypertension and type 2 diabetes mellitus, conditions that significantly elevate the risk of MCI. Moreover, it stimulates the release of nitric oxide, enhancing arterial elasticity and reducing blood pressure. At a molecular level, it is hypothesized that aerobic exercise modulates the activation of microglia and astrocytes, cells crucial to brain inflammation and neurogenesis, respectively. It has also been suggested that aerobic exercise promotes the release of exercise factors such as irisin, cathepsin B, CLU, and GPLD1, which could enhance synaptic plasticity and neuroprotection. Consequently, regular aerobic exercise could potentially prevent or reduce the likelihood of MCI development in elderly individuals. These molecular mechanisms, however, are hypotheses that require further validation. The mechanisms of action are intricate, and further research is needed to elucidate the precise molecular underpinnings and to develop targeted therapeutics for MCI.